Sale and Purchase of Agricultural Fertilizer with a Debt System with an Islamic Law Perspective in Andalas Cermin Village, Rawa Pitu District, Tulang Bawang Regency - Kholidin; Hidayatullah, Kholid; Wijaya, Muhamad Rudi (Journal Tafkirul Iqtishodiyyah, 2021)
There are two problem formulations that the author will discuss in the practice of buying and selling agricultural fertilizers with a debt system in Andalas Cermin Village, Rawa Pitu District Tulang Bawang Regency. That is how the system of buying and selling agricultural fertilizers with a debt system in Andalas Cermin Village, whether buying and selling agricultural fertilizers with a debt system in Andalas Cermin Village is in accordance with Islamic law. This research aims to increase knowledge of Islamic law for sellers and buyers of agricultural fertilizers in implementing buying and selling using a debt system, so that their business can run in accordance with Islamic law. The research conducted is field research that collects qualitative data. That is data obtained directly from primary data both from the seller and the buyer, and also from secondary and tertiary data. This research uses observation, interview and documentation data collection techniques, then all the data will be analyzed inductively to draw conclusions The results showed that: The practice of buying and selling agricultural fertilizers on debt in Andalas Cermin village is that some people use the Pay harvest system payment, due to the economic conditions of most of the underprivileged people and also other needs, including school fees, rice field maintenance costs, and other needs. other. The sale and purchase of agricultural fertilizers with a debt system in the village of Andalas Cermin when viewed from the practice has fulfilled the pillars and conditions of buying and selling, and is in accordance with Islamic law. The value contained in Islamic law is the value of maslahah because it can facilitate and help farmers, and buying and selling this system is also included in 'urf because the system of buying and selling agricultural fertilizers with a debt system has become a habit for most people in the Andalas Cermin village. note-taking system is not in accordance with sharia economic law